Prostatic arterial embolization as a micro-invasive treatment option for benign prostatic obstruction: A subtle balance between short-term follow-up patient-reported outcomes and de-obstructive effectiveness - Bertolo, Riccardo; Cipriani, Chiara; Giuliani, Maria Silvia; Maiorino, Francesco; Vittori, Matteo; Carilli, Marco; Signoretti, Marta; Minucci, Sergio; Bove, Pierluigi (Frontiers in Urology, 2022)
Purpose The study evaluated the effectiveness of prostatic arterial embolization (PAE) in the relief of benign prostatic obstruction (BPO) beyond the patient-reported outcomes. Methods Retrospective evaluation of patients who underwent PAE (March 2015–December 2019). All patients underwent prostate MRI to assess prostate volume (PVol), uroflowmetry to assess Qmax, and were administered IPSS + QoL. MRI, and IPSS were repeated 3 months postoperatively. Patients were contacted for urological consultation, including uroflowmetry with post-voiding residual volume (PVR), IPSS + QoL. Additionally, patient satisfaction was assessed. Sexual function, including ejaculation and complications, was recorded. Results Fifty-two patients were analyzed. At baseline, PVol was 66 ml (IQR 48–67), Qmax 13.5 ml/s (IRQ 11.5–19), IPSS 23 (IQR 18–25), and QoL 4.5 (IQR 4–5). At 3-month follow-up, MRI showed a 27% (IQR 18–36) reduction in PVol (p <0.001). The IPSS decreased by 81% (IQR 58–91, p <0.001). At a median follow-up of 14 months (IQR 10.5–27.5), IPSS decreased by 40% (IQR 26–54, p <0.001) and QoL by 50% (IQR 20–75, p = 0.002) versus baseline. The absolute Qmax was 12.2 ml/s (IQR 9.5–14). Median %variation of Qmax vs baseline was −7.3% (IQR −33.9; +25.5, p = 0.7). All sexually active patients maintained ejaculation. Thirty-eight (73%) were satisfied with the treatment they received. One patient reported post-operative erectile dysfunction. All patients who were counseled for adjuvant endoscopic treatment refused surgery except for one. Conclusion In our analysis, PAE provided significant improvement in the short-term follow-up patient-reported outcomes. Most patients were satisfied, and ejaculation was maintained. On the other hand, the effectiveness of PAE on the relief of BPO seemed virtually intangible in most of the cases.